Prevalence of Acute Coronary Syndrome among Patients Presenting with Chest Pain - Akhtar Sher, Muhammad Ahsan Bashir, Sobia Humerah, Muhammad Rehan Khan, Namra Sohail Raja, Iftikhar Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Multiple organ diseases can cause chest pain. One of the most important differential diagnoses is acute coronary syndrome (ACS). The present study aim was to determine the incidence of ACS among patients presented with chest pain. Patients and Methods: This observational study was carried out on 168 patients presented with chest pain in the Department of Cardiology, DHQ Teaching Hospital / GKMC, Swabi and Punjab Institute of Cardiology Lahore. The duration of study was 6 months from October 2021 to March 2022. Chest pain, diabetes, hypertension, and smoking status from each individual were recorded. The incidence of ACS was determined. Patients presented with chest pain and had >16 years age were enrolled. Thoracic patients, traumatic chest pain, and local infectious patients were excluded. Nature of chest pain such as substernal pain, nitroglycerin relieved pain, and exertion provoked pain were assessed. ACS was diagnosed and confirmed by electrocardiograph (ECG), prior history, and cardiac biomarkers. Descriptive statistics was carried out in SPSS version 26. Results: Of the total patients, there were 116 (69%) male and 52 (31%) females. The prevalence of acute coronary syndrome was 62 (36.9%) among patients presented with chest pain. The overall mean age was 46.82±12.1 years with age range from 16 years to 80 years. The incidence of diabetes, hypertension, and smoker were 48 (28.6%), 66 (39.3%), and 38 (22.6%) respectively. Out of 168 patients, the prevalence of non-specific, atypical, and typical chest pain was 88 (52.3%), 50 (29.8%), and 30 (17.9%) respectively. Of the total 62 ACS patients, the incidence of STEMI, NSTEMI, and unstable angina were 28 (45.2%), 19 (30.6%), and 15 (24.2%) respectively. Conclusion: The present study found that the incidence of ACS was 36.9% among patients presented with chest pain. Acute coronary syndrome was the most important differential diagnoses in chest pain patients. If a patient is presenting with chest pain, the diagnosis of ACS needs to be strongly deduced, and prompt action taken so that the patient can undergo proper treatment as soon as possible. Keywords: Acute coronary syndrome, Chest pain, Prevalence